The Effect of Social Support, Job Stress, and Job Satisfaction on Employee Mental Health in the Creative Industry in Jakarta - Situmorang, Rupina Kanasia; Febriyanto, Weda; Kurniawan, Kurniawan (Westscience Press, 2024)
This study explores the impact of social support, job stress, and job satisfaction on employee mental health within Jakarta's creative industries. Employing a quantitative research design, data were collected from 200 employees using a Likert scale questionnaire. The relationships between the variables were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings indicate that all hypotheses are positive and significant, with job satisfaction emerging as the strongest predictor of employee mental health. Interestingly, job stress, while typically associated with negative outcomes, also showed a positive relationship with mental health in this context, suggesting a complex interaction where stress may act as a motivator. Social support, though slightly less influential, was found to significantly enhance mental well-being by providing a protective buffer against the demands of creative work. These results underscore the importance of fostering job satisfaction, managing job stress, and promoting a supportive work environment to improve mental health outcomes in Jakarta's creative industries.